Higher education and indigenous peoples: national contexts to place the experiences - Olivera Rodríguez, Inés (2017)
In order to provide a contextual frame to understand and to compare the experiences analyzed in this issue, this introductory text presents the situation indigenous youth is facing in higher education in Mexico and Peru. This contextual presentation has been shaped by our conviction that what has been achieved is a result of a larger process of indigenous struggles and claims, their translation into public policy and its implementation inside higher education institutions. Accordingly, this text introduces the cases of Mexico and Peru through two dimensions: the emergence of the specific claims, on the one hand, and the respective construction of intercultural higher education for indigenous people, on the other hand.